The Use of the internet in learning by islamic school teachers - Sri Sunarti (12 Waiheru, 2024)
The Internet is relatively easy because it has become part of the work routine in all fields, especially education. The Internet allows teachers to deliver lesson material more easily and quickly, making learning more accessible and enjoyable. This research aims to determine the ability of Islamic school teachers to use the Internet in learning. This research uses a descriptive quantitative method by distributing some questionnaires about using the Internet in learning, totalling 22 questions. The research results show that around 17% of Islamic school teachers strongly agree with using the Internet, more than 50% of teachers state agree, 20% disagree, and only 3% strongly disagree. This means that some Islamic school teachers need to gain competence in using the Internet, and most Islamic school teachers use it in the learning process as part of the learning resources because of their competence.